Discovering hidden treasures: unveiling a new population of the narrow endemic Hieracium lucidum Guss. (Asteraceae) on the Mounts of Palermo (NW Sicily, Italy) - Pasta, Salvatore; Gristina, Alessandro Silvestre; Marcenò, Corrado; De Simone, Leopoldo; Garfì, Giuseppe; Giacalone, Gabriele; Ilardi, Vincenzo; Kozlowski, Gregor; Scuderi, Leonardo; Guarino, Riccardo (Hacquetia, 2024)
The authors discovered a new population of Hieracium lucidum Guss., a species hitherto considered strictly endemic to Monte Gallo. Useful elements for the ecological characterisation of the new population are provided. The stretch of carbonate coastline between the Egadi Islands and the western portion of the Province of Palermo displays a very high wealth of valuable floristic elements and represents a unicum in terms of both phytogeography and ecology. Considering the extreme fragmentation of the distribution pattern of many endemic and exclusive species that characterise this district, as in the case of H. lucidum, the authors suggest upgrading the strategies to protect the local botanical heritage, going beyond the species approach and thinking on a wider territorial scale.